Thread Threat - Sofokleous, Konstantina (My University, 2021)
Wholly filmed on top of a doll silhouette, an interpretation of the 1810 Grimm handwritten manuscript of 'Snow White'*, concentrating on the cruelty of Snow White's biological mother.
Keywords: Animated Film